Synthesis of barium ferrite ultrafine powders by a sol–gel combustion method using glycine gels - Jiao, D.L. (2014)
The ultrafine powders of barium ferrite (BaFe12O19) were synthesized by a sol–gel combustion technique using glycine gels prepared from metal nitrates and glycine solutions. The effects of processing parameters such as initial Fe/Ba molar ratio, the dosage of glycine and calcination temperature on the crystalline phase formation, microstructure and magnetic properties were systematically investigated. The results showed that the formation of single-phase barium ferrite is significantly influenced by Fe/Ba molar ratio which is the optimum at 9/1. The XRD patterns revealed that high calcination temperature and large glycine dosage are beneficial for the formation of barium ferrite. The TEM and size distribution demonstrated that the BaFe12O19 powders have plate-like shape with crystallite size varied from 55 to 110 nm. The products with high coercive force of 5750 Oe and saturation magnetization of 67.7 emu/g were obtained when the glycine/nitrates molar ratio and calcination temperature are 12/9 and 900 °C, respectively.